A critical review on risk evaluation and hazardous management in carcass burial - Chowdhury, Saikat; Kim, Geon-Ha; Bolan, Nanthi; Longhurst, Philip J. (Elsevier, 2019)
Carcass disposal from livestock disease outbreaks or on-farm, routine mortalities present a number of challenges. Proper management of carcasses can no longer be addressed as an incidental occurrence, as they represent a persistent pathway of infectious agricultural wastes with potential to harm the environment. The long-term management of carcass disposal sites is essential irrespective of the cause of mortality. Critically this ensures eradication of disease and environmental protection from a range of biological and chemical hazards. Strategies for large-scale carcass disposal require preparation and coordinated, proactive planning in advance of emergencies to meet environmental protection guidelines and maximize the efficiency of response. Carcass disposal methods include burial, incineration, composting, alkaline hydrolysis, lactic acid fermentation and anaerobic digestion. Burial techniques include trench burial, landfill, and notably mass burial as one of the most common methods of disposal. However, there are concerns about possible impacts to the environment and subsequent risk to human health regardless of the initial logistical and economic advantages. This review provides an overview of our current understanding of the potential threats of carcass burial and possible management options. The environmental implications of terminating burials is discussed as is the role of biochar and phytoremediation which can contribute to the management of burials. These examples are considered in the case study context of Korea where long-term considerations remain a priority. The outcome of the review is structured to provide information to decision-makers that is of value when equipping themselves with comprehensive guidelines for the sustained management of carcass burials. Finally, recommendations that address future research needs are outlined.
Keywords: Carcass burial; Groundwater remediation; Livestock disease; Mortality disposal; Risk assessment